Interpretasi Visual dan Digital untuk Klasifikasi Tutupan Lahan di Kabupaten Kuningan, Jawa Barat - Dede Kosasih; Muhammad Buce Saleh; Lilik Budi Prasetyo (Jurnal Ilmu Pertanian Indonesia, 2019)
Land cover information are needed to support decision making process on natural resource management. Remote sensing has been provideingr a huge distribution of geographical land cover information on various spatial scales. Landsat 8 OLI can be used on various applications and researches, including on land cover classification. Parameters used on land cover identification can be extracted from Landsat 8 OLI (Operational Land Imager). The research tried to explore land cover classification in Kuningan District by using two different classification methods, visual and digital maximum likelihood using Landsat 8 OLI acquired on August 5th2014. The main objectives of the research were to develop land cover map and assess the result accuracy on both different methods used. Confusion matrix using Overall accuracy and Kappa value was used as a reference on defining the accuracy. As a result, visual interpretation identified 10 land cover classes with Overall accuracy of 94.02% and Kappa value of 0.93. While digital maximum likelihood identified 10 land cover classes with Overall accuracy of 93.17% and Kappa value of 0.92.